Apoptosis-inducing activity and tumor-specificity of antitumor agents against oral squamous cell carcinoma - Hiroshi Sakagami (Elsevier, 2010)
This review searched previous works of apoptosis induction in human oral squamous cell carcinoma (OSCC) cells. Many chemotherapeutic drugs, natural products, metabolic inhibitors, hormone receptor ligands and gene manipulations induced the apoptosis directly or indirectly by reverting the anti-apoptotic pathways. However, these antitumor agents, sometimes induced incomplete apoptosis or other types of cell death characterized by lack of caspase activation and internucleosomal DNA fragmentation, depending on the target cells or the chemical structure of inducers. There were very few investigations that have compared the cytotoxicity of these antitumor substances against OSCC cells with that of normal oral cells. Furthermore, their apoptosis-inducing activity has not been correlated well with tumor-specificity (higher cytotoxicity against tumor cells versus normal cells). These accumulated evidences provide the cautionary note against the apoptosis-oriented research.